2002
DOI: 10.1289/ehp.02110549
|View full text |Cite
|
Sign up to set email alerts
|

Children's exposure to chlorpyrifos and parathion in an agricultural community in central Washington State.

Abstract: We measured two diethyl organophosphorus (OP) pesticides--chlorpyrifos and parathion--in residences, and their metabolic by-products, in the urine of children 6 years old or younger in a central Washington State agricultural community. Exposures to two dimethyl OP pesticides (azinphos-methyl and phosmet) in this same population have been reported previously. We categorized children by parental occupation and by household proximity to pesticide-treated farmland. Median chlorpyrifos house dust concentrations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
179
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(188 citation statements)
references
References 7 publications
(9 reference statements)
8
179
1
Order By: Relevance
“…A recent longitudinal study of the urinary OP metabolite levels of children living in an area where OP pesticides are used in agriculture found that the metabolite concentrations were higher in months when OPs were used on orchards, despite no direct contact of family members with the pesticides or location near the sprayed orchards (Koch et al, 2002). In a study of CPF levels in house dust compared to urinary TCP levels for children of pesticide applicators, farm workers, and nonagricultural workers, urinary TCP did not match well the parental occupation, although it did match home garden pesticide use (Fenske et al, 2000(Fenske et al, , 2002b. Observed levels of TCP may not match well the potential intake of CPF in nonacute exposure settings.…”
Section: Biomarkers Of Exposurementioning
confidence: 99%
“…A recent longitudinal study of the urinary OP metabolite levels of children living in an area where OP pesticides are used in agriculture found that the metabolite concentrations were higher in months when OPs were used on orchards, despite no direct contact of family members with the pesticides or location near the sprayed orchards (Koch et al, 2002). In a study of CPF levels in house dust compared to urinary TCP levels for children of pesticide applicators, farm workers, and nonagricultural workers, urinary TCP did not match well the parental occupation, although it did match home garden pesticide use (Fenske et al, 2000(Fenske et al, , 2002b. Observed levels of TCP may not match well the potential intake of CPF in nonacute exposure settings.…”
Section: Biomarkers Of Exposurementioning
confidence: 99%
“…CPF and its metabolites have been detected in farm animals, such as cattle, hogs and sheep (Ivey 1979;Ivey and Palmer 1979;Ivey and Palmer 1981). Moreover, chlorpyrifos residues or its metabolites have been discovered in the diet of preschoolers (Fenske et al 2002a), in the urine of children living in proximity to orchards (Lu et al 2000;Fenske et al 2002b), as well as in the cord blood of infants born to minority women living in urban settings (Whyatt et al 2004). …”
Section: Introductionmentioning
confidence: 99%
“…Indoor concentrations of pesticides in proximity to pesticidetreated farmland have been measured (Fenske et al, 2002). For example, it has been shown that pesticide exposure in children could potentially be increased if they live in homes in close proximity (60 m) to pesticide-treated farmland (Fenske et al, 2002).…”
Section: Indoor Exposure Pathwaysmentioning
confidence: 99%
“…For example, it has been shown that pesticide exposure in children could potentially be increased if they live in homes in close proximity (60 m) to pesticide-treated farmland (Fenske et al, 2002). Clothing and cars of farm workers can also be a source of pesticide exposures for children.…”
Section: Indoor Exposure Pathwaysmentioning
confidence: 99%